Sexual Education for Parents and Teachers of Teenagers with Special Needs - Penny Handayani; Weny Savitry S. Pandia; Agustin Angelia Putri; Lidia Wati; Vincentia Visi P; Agatha Rizky (Institute for Research and Community Services, 2019)
Yayasan Wahana Inclusive Indonesia (YWII) is an institution engaged in providing services for children with special needs, people with disability, and inclusive society. YWII provides services that include counseling, development of individual learning programs (PPIs), support services for children with special needs, and training for educators, schools, parents, and communities. Educational and training activities are conducted by helping children with special needs to learn a few things they need most in their daily lives. Based on the children’s needs, the Master’s Program of Child and Adolescent Psychology Professionals, Faculty of Psychology, Atma Jaya Catholic University, designed training-based interventions to improve the knowledge of students, teachers, and parents about sexual behaviors. Prior to the intervention, the researcher conducted an assessment to determine the causes of